Content-Based Instruction: A Relevant Approach of Language Teaching - Bula Villalobos, Olmedo (Innovaciones Educativas, 2014)
Content-Based Instruction is an approach in which the teaching is organized around the content. Likewise, the principles of Content-Based Instruction are heavily rooted on the principles of communicative language teaching since they involve an active participation of students in the exchange of content. This article reflects upon Content-Based Instruction as a relevant language teaching approach, its background, the definition of the concept, and its principles. Moreover, the article reports on Content-Based Instruction’s distinctive characteristics and its main models. Additionally, a Content-Based Instruction lesson plan with its materials is provided. Finally, a set of conclusions and implications is also discussed.